The SCUBA-2 cosmology legacy survey: ALMA resolves the rest-frame far-infrared emission of sub-millemeter galaxies - Simpson, J.M.; Smail, Ian; Swinbank, A.M.; Almaini, O.; Blain, A.W.; Bremer, M.N.; Chapman, S.C.; Chen, Chian-Chou; Conselice, Christopher J.; Coppin, K.E.K.; Danielson, A.L.R.; Dunlop, J.S.; et al. (American Astronomical Society, 2015)
We present high-resolution (0’’.3) Atacama Large Millimeter Array 870 μm imaging of 52 sub-millimeter galaxies (SMGs) in the Ultra Deep Survey field to investigate the size and morphology of the sub-millimeter (sub-mm) emission on 2–10 kpc scales. We derive a median intrinsic angular size of FWHM = 0’’.30 ± 0’’.04 for the 23 SMGs in the sample detected at a signal-to-noise ratio (S/N) >10. Using the photometric redshifts of the SMGs we show that this corresponds to a median physical half-light diameter of 2.4 ±0.2 kpc. A stacking analysis of the SMGs detected at S/N < 10 shows they have sizes consistent with the 870 μm bright SMGs in the sample. We compare our results to the sizes of SMGs derived from other multi-wavelength studies, and show that the rest-frame ∼250 μm sizes of SMGs are consistent with studies of resolved 12CO (J = 3–2 to 7–6) emission lines, but that sizes derived from 1.4 GHz imaging appear to be approximately two times larger on average, which we attribute to cosmic ray diffusion. The rest-frame optical sizes of SMGs are around four times larger than the sub-millimeter sizes, indicating that the star formation in these galaxies is compact relative to the pre-existing stellar distribution. The size of the starburst region in SMGs is consistent with the majority of the star formation occurring in a central region, a few kiloparsecs in extent, with a median star formation rate surface density of 90 ± 30M_ yr−1 kpc−2, which may suggest that we are witnessing an intense period of bulge growth in these galaxies.